RETROSPECTIVE EVALUATION OF DIFFERENT FODDER REGIMENS AND CLIMATE ON PREGNANCY RATE IN JERSEY CROSSBRED COWS OF SUBTEMPERATE REGION - SOOD, PANKAJ; THAKUR, Y P; SINGH, MADHUMEET; RANI, DESY; BURMAN, POORBI; RUTHWAL, ANOOP; SHARMA, RAJESH; KUMAR, NAVEEN (The Indian Journal of Animal Reproduction, 2023)
The present study compared separately a retrospective assessment of association of 17 different fodder regimens and three different classes of temperature - humidity index (THI) with per cent pregnancy rates (PRs), following 3,264 artificial inseminations (year 1998 to 2008) in Jersey crossbred cows. The similar fodder combinations and THI were separately clubbed on monthly basis for their association with PR. The green fodder(s) offered to the cows comprised of maize, oats and other green fodders (OGF) namely Seteria, Napier, Kikuyu, Berseem and Sorghum. In addition, silage and wheat straw were also supplemented. The two highest PRs of 41.4% and 40.9% were associated, respectively, with feeding of fodder combinations having 36.3% and 35.4% silage of the total fodder, respectively. Considered together, feeding different fodder combinations of greens having 38.8% to 95.1 % maize resulted in a PR of 32.8%, which was less (P=0.10) than 37.5% as recorded with other fodder combinations not having maize. The PR at different THI categories of 50-60, 61-70 and 71-75, respectively, were similar and ranged from 35.0 to 38.0%. In conclusion, pregnancy rates were higher in cows provided silage with green fodder than the others given maize fodder dominated diets. The latter needs to be investigated for the associated mechanism(s) reducing pregnancy rates.